The role of gonadotropin-releasing hormone agonists in female fertility preservation - Lee, Jae Hoon (Clin Exp Reprod Med, 2021)
Advances in anticancer treatments have resulted in increasing survival rates among cancer patients. Accordingly, the quality of life after treatment, particularly the preservation of fertility, has gradually emerged as an essential consideration. Cryopreservation of embryos or unfertilized oocytes has been considered as the standard method of fertility preservation among young women facing gonadotoxic chemotherapy. Other methods, including ovarian suppression and ovarian tissue cryopreservation, have been considered experimental. Recent large-scale randomized controlled trials have demonstrated that temporary ovarian suppression using gonadotropin-releasing hormone agonists (GnRHa) during chemotherapy is beneficial for preventing chemotherapy-induced premature ovarian insufficiency in breast cancer patients. It should also be emphasized that GnRHa use during chemotherapy does not replace established fertility preservation methods. All young women facing gonadotoxic chemotherapy should be counseled about and offered various options for fertility preservation, including both GnRHa use and cryopreservation of embryos, oocytes, and/or ovarian tissue.